Pengaruh DER, ROA, SIZE, EPS, cash position dan TATO terhadap DPR perusahaan manufaktur Periode 2016-2019 - Nurul Hasanah Harahap, Qori; Br Situmorang, Monika; Karina Br Karo, Fristalia; Hayati, Keumala (Jurnal Paradigma Ekonomika, 2021)
The purpose of this study is to examine the effect of DER, ROA, Firm Size, EPS, Cash Position, and Total Asset Turnover using the t-test and F test. This study uses quantitative descriptive. The number of manufacturing companies used as a population is 169 companies selected based on purposive sampling obtained a sample of 54 companies. The data analysis technique used is multiple linear regression analysis. The results of data analysis partially show that only DER has a significant negative impact on DPR. Simultaneously, six independent variables have a substantial effect on the DPR. The coefficient of determination test results shows the Adjusted R Square number of 0.108, which means 10.8% of the variation from the DPR of manufacturing companies, which can be explained by the independent variables used. The remaining 89.2% is caused by other factors such as Growth Opportunity, Ownership, Current Ratio, and others. Â